PENGARUH DISIPLIN DAN MOTIVASI TERHADAP KINERJA KARYAWAN - Mr Wahyudi (Sekolah Menengah Kejuruan (SMK) Pustek, 2019)
The poor performance of employees is not just a matter of attitude, other things like not reaching the target and customer complaints. Therefore a performance study is needed, and this study specifically examines the effect of motivation and discipline on performance. The quantitative approach is used, the research method uses associative causal, the analysis unit is a bank employee, and the research instrument uses a questionnaire with a Likert scale. The analysis method used is multiple linear regression analysis with a sample of 52 and the sampling technique used is a saturated sample technique. Furthermore, the research was carried out by testing with the stages of analysis that included descriptive analysis, validity test, reliability test, linear regression test, correlation coefficient test, simultaneous test and test coefficient of determination. The results showed that the contribution of motivation and discipline to performance was significant. This finding explains that performance will not be achieved if one of them lacks motivation and discipline rules